Research on the Status and Countermeasures of After-school Extended Hours Service in Yunnan Primary Schools: – Zhaotong City as an Example - Yu, Qiumei; Jiang, Zhongdan; Gao, Yi; Ai, Yingtong (Transactions on Economics, Business and Management Research, 2023)
Objective: Under the background of the "Double Reduction Policy", there is a mismatch between the time when primary school students leave school and the time when parents go off work, and picking up and dropping off children on time has become a problem for people’s livelihoods. In order to solve the "three and a half hours" problem derived from this, and to further enhance the capacity of education services, the Ministry of Education issued a relevant document in 2017 to encourage the provision of custodial after-school services by schools. In order to solve the "3:30" problem and further enhance the capacity of education services, the Ministry of Education issued a relevant document in 2017, encouraging schools to provide custodial after-school services. With the support of this document, and adhering to the principle of "one school, one case", schools around the world have implemented after-school extended hours services. This study takes Zhaotong City, Yunnan Province, as an example, and uses questionnaire survey method and interview method to survey 262 primary school students and 18 teachers within Zhaotong City to understand the current situation of after-school extended hours service implementation. The survey found that the after-school extended hours service in Yunnan primary schools exists problems such as lack of characteristics in content, imperfect infrastructure configuration, low motivation of participating teachers and insufficiently strong school management. In response to the above problems, the survey proposes countermeasures such as relying on the existing conditions to explore curriculum resources, improving the basic configuration of after-school extended hours service, strengthening the management of after-school extended hours service in schools, and improving the systematic guarantee of after-school extended hours service. In order to provide a certain reference for the development of after-school extended hours service in Yunnan primary schools.